2010
DOI: 10.1007/s13304-010-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiological estimation of size in colorectal liver metastases: is it reliable? Comparison with post-resectional measurements

Abstract: Since the efficiency of percutaneous ablation techniques in treating colorectal liver metastases is dependent on tumor size, the aim of this study was to verify the accuracy of computed tomography or magnetic resonance in estimating the maximum diameter of colorectal liver metastases by comparing these findings with those of pathology in a series of patients who underwent liver resection. Radiological and pathological tumor measurements in 39 patients operated for 69 colorectal liver metastasis were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This tumor assessment is compatible with the definitions of mRECIST. 15 It has been reported that there exists a reliable correlation between the results of pretransplant imaging and explant/resection pathology regarding the size of viable tumors, [28][29][30] as shown in the present study. In patients who had undergone TACE before LT, the TV can be estimated through volumetric measurement of the contrast-enhancing portions of tumors and lipidolized zones were considered non-enhancing lesions as adopted in the mRECIST criteria, 30 which can offset the different therapeutic effects of preceding HCC treatments.…”
Section: Discussionsupporting
confidence: 76%
“…This tumor assessment is compatible with the definitions of mRECIST. 15 It has been reported that there exists a reliable correlation between the results of pretransplant imaging and explant/resection pathology regarding the size of viable tumors, [28][29][30] as shown in the present study. In patients who had undergone TACE before LT, the TV can be estimated through volumetric measurement of the contrast-enhancing portions of tumors and lipidolized zones were considered non-enhancing lesions as adopted in the mRECIST criteria, 30 which can offset the different therapeutic effects of preceding HCC treatments.…”
Section: Discussionsupporting
confidence: 76%
“…10 The comparison of radiologic-pathologic tumor measurements conducted in several other cancers has demonstrated that radiologic measurement significantly corresponded with pathologic tumor size and may be valuable in treatment planning. [24][25][26][27][28][29] To our knowledge, however, no previous study has provided and directly correlated the measurement data between the solid component of subsolid nodules on thin-section CT and the invasive component on pathologic exams. Therefore, the purpose of our study was to evaluate the correlation between the size of the solid component on thinsection CT and the invasive component on pathology in small lung adenocarcinomas and preinvasive lesions manifesting as subsolid nodules.…”
mentioning
confidence: 99%
“…TV in HCC patients who had undergone TACE before HR can be estimated by measuring the volumes of the contrast‐enhancing portions of tumors, with lipidolized zones considered non‐enhancing lesions according to modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria, 9 offsetting the therapeutic effects of locoregional treatments. Reliably high correlations in the sizes of viable tumors were observed between preoperative imaging results and explant/resection pathology 10–12 . Our previous study with 843 liver transplant recipients revealed that comparison of the preoperative imaging and postoperative pathology findings showed high correlation regarding viable tumor numbers ( ρ = .845, p < .001), maximal tumor size ( ρ = .688, p < .001), total TV ( ρ = .736, p < .001), and ADV score ( ρ = .895, p < .001) 7 .…”
Section: Discussionmentioning
confidence: 74%
“…Reliably high correlations in the sizes of viable tumors were observed between preoperative imaging results and explant/ resection pathology. [10][11][12] Our previous study with 843 liver transplant recipients revealed that comparison of the preoperative and postoperative pathology findings showed high correlation regarding viable tumor numbers (ρ = .845, p < .001), maximal tumor size (ρ = .688, p < .001), total TV (ρ = .736, p < .001), and ADV score (ρ = .895, p < .001). 7 Therefore, preoperative ADV scores based on imaging analyses and postoperative ADV scores based on pathologic findings are comparable, with both resulting in similar prognostic outcomes.…”
Section: Discussionmentioning
confidence: 96%